The impact of an irrigation scheme on crop production and farmer's income in Khost Province, Afghanistan - Rahman, Mujeeb; Thapa, Gopal B.; Soparth Pongquan; Datta, Avishek; AIT-Ministry of Higher Education (MOHE), Afghanistan Partnership Project (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
As more than half of the Afghan population are engaged in the agriculture productivity andrelied on farm production for their household livelihood. Therefore, during a decadenumbers of irrigation systemsare constructed and rehabilitated to improve rural livelihoodthrough increase crop production andincrement of household income. This study analyzedthe impact of irrigation water scheme in comparison to before and after operation of theirrigation system on farmer access to adequate irrigation water, crop production, householdemployment, food consumption and household income. Using primary data collected from120 householdsthat is equivalent to11.2 % of the total population of seven villages suchas,Babar, Hajino, Wadate, Malakan, Lalash, Digan and Layere of Lakan area withclassified of the upper, middle and lower sections of the irrigation system, through thestandardize questionnaire, group discussion and key informant interview. The findings ofstudy revealed that irrigation system had positive effect in improvement of farm activities.Therefore, with availability of irrigation water the fallow lands were irrigated in the upper,middle and lower sections of the irrigation system in the study area.However, in thecontext of accessibility to irrigation water, farmers in the upper and middle sections hadeasier access to adequate irrigation water and fairly better benefited than those in the lowersection. Due to adequacy of irrigation water majorityof farmers{u2019} focused on cultivation ofhigh economic value crop such as rice in the upper and middle sections in summer season.Vis-à-vis in the lower section a greater proportion of farmers were concentrated oncultivation of maize crop because of shortage of irrigation water for their farming.Fundamentally, provision of irrigation water positively changed and increased yield ofmain cereal crops such as wheat, rice, maize and mungbean that affected food consumptionand household income in the study area. However, inequality in accessibility to irrigationwater created variation in food consumption and households{u2019} income among the upper,middle and lower sections of the irrigation system. Therefore, owing to adequate irrigationwater, majority of the households in the upper and middle sections addressed their requiredfood consumption ration 195 kg/person /year, while in the lower section due to shortage ofirrigation water during cropping seasons (winter and summer) roughly half of the surveyedhouseholds remained in inadequacy of consumption food due to low harvesting from theirfarm.Moreover, households{u2019} income in the upper and middle sections significantly increased dueto cultivation of high economic value crop of rice in comparison to lower section.It mayconcluded that low amount of crops harvesting obligated farmer households{u2019} in the lowersection to engage with high labor force in farm activities in comparison to upper andmiddle sections which resulted in less households{u2019} income. Irrigation water was not scarcebut poor management of the irrigation system was the cause of inequity access to adequateirrigation water that resulted in a decline in crop production and household income in thestudy area.Based on the findings of this study, establishment of water use associations andfair waterdistribution mechanism are suggested to improve management of the irrigation system andenhance equity access to adequate irrigation water throughout the study area. Allocation ofirrigation water through identification of landholding size, and distribution based on timeinterval may improve equitable access of farmers{u2019} to irrigation water for their farming.
A thesis submitted in partial fulfillment of therequirements for thedegree of Master of Science in Regional and Rural Development Planning
Thesis (M. Sc.) - Asian Institute of Technology, 2014
Keywords: Farmers -- Afghanistan -- Khost -- Economic conditions; Crops -- Irrigation -- Afghanistan -- Khost